2017
DOI: 10.1021/acs.organomet.7b00398
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Iron Hydride Complexes Relevant to Hydrogen Isotope Exchange in Pharmaceuticals

Abstract: Addition of H 2 gas to the bis(arylimidazolin-2-ylidene)pyridine iron bis(dinitrogen) complex (H 4 -iPr CNC)Fe(N 2 ) 2 resulted in facile oxidative addition of the H−H bond to yield a mixture of (H 4 -iPr CNC)FeH 4 and trans-(H 4 -iPr CNC)FeH 2 (N 2 ), depending on the partial pressures of H 2 and N 2 . Both iron hydride complexes were characterized by X-ray diffraction and proved relevant to the catalytic hydrogen isotope exchange of arene C(sp 2 )−H bonds. Activation of the benzene-d 6 solvent at ambient tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…The exact mechanism was not identified in their original publication, and in a following study it was found that FeD 4 (CNC-ligand) and FeD 2 N 2 (CNC-ligand) are active intermediates, which form through a facile oxidative addition of the initial catalyst to the D-D bond. 44 In 2018, the same group reported a Ni-catalyzed site-selective HIE reaction of C(sp 2 )-H bonds in nitrogen heteroarenes. 45a An -diamine nickel hydride complex offered Q.-K. Kang, H. Shi Cluster Synlett a distinct site selectivity with other HIE metal catalysts, such as Crabtree's and Kerr's iridium species (Scheme 15a).…”
Section: Other Metalsmentioning
confidence: 99%
“…The exact mechanism was not identified in their original publication, and in a following study it was found that FeD 4 (CNC-ligand) and FeD 2 N 2 (CNC-ligand) are active intermediates, which form through a facile oxidative addition of the initial catalyst to the D-D bond. 44 In 2018, the same group reported a Ni-catalyzed site-selective HIE reaction of C(sp 2 )-H bonds in nitrogen heteroarenes. 45a An -diamine nickel hydride complex offered Q.-K. Kang, H. Shi Cluster Synlett a distinct site selectivity with other HIE metal catalysts, such as Crabtree's and Kerr's iridium species (Scheme 15a).…”
Section: Other Metalsmentioning
confidence: 99%
“…Formation of free H─D is proposed to occur through an oxidative addition-reductive elimination sequence, similar to that observed with the isoelectronic (H 4 -iPr CNC)Fe(N 2 ) 2 . 66 Further demonstration of the oxidative addition reactivity of the ( Mes-CCC)CoN 2 (PR 3 ) (R = Ch 3 , Ph) family of complexes was demonstrated by addition of HCl to the PMe 3 derivative to form the cobalt(III) product, ( Mes CCC)CoH(Cl) (PMe 3 ) (Scheme 12a). In addition, ( Mes CCC)CoN 2 (PPh 3 ) has been found to be an efficient precatalyst for alkene hydrogenation and para-hydrogen induced polarization (PHIP) NMR experiments support oxidative addition of H 2 to form Co(III) (Scheme 12b).…”
Section: Oxidative Addition With Cobalt(i)mentioning
confidence: 99%
“…One salient question was the role of oxidative additionboth of H 2 (or isotopologue) and of the C–H bondand what role, if any, these fundamental transformations played in the improved activity at lower gas pressure and on site selectivity. To answer this question, our laboratory conducted studies with the HIE precatalyst (H 4 - iPr CNC)­Fe­(N 2 ) 2 and dihydrogen . Immediately upon exposure to H 2 in benzene- d 6 , two new iron hydride products were observed by 1 H NMR spectroscopy and ultimately characterized by single-crystal X-ray diffraction.…”
Section: Exploring Oxidative Addition With Iron: From Redox-active Py...mentioning
confidence: 99%
“…This applies even more to CNC pincer-type ligands with saNHC or benzNHC congeners [45][46][47][48][49][50]. In fact, only one example has been reported for the saNHC derivatives, which is Chirik's iron complex [51,52]. This iron complex was synthesized by in situ deprotonation/metalation using iron hexamethyldisilazane (Fe[N(SiMe 3 ) 2 ] 2 ) as a precursor.…”
Section: Introductionmentioning
confidence: 99%